A supported oxygen-containing copper cluster catalyst and its application in electrocatalytic synthesis of methane
Patent Information
- Application Number
- CN202610679350.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明的目的是提供一种负载型含氧铜团簇催化剂及其在电催化合成甲烷中的应用,以解决现有技术中铜基催化剂在高电流密度下甲烷选择性与长期稳定性难以兼顾的问题
[0018]与现有技术相比,本发明提供的一种负载型含氧铜团簇催化剂及其在电催化合成甲烷中的应用,通过将含氧铜以团簇形式负载于稀土金属氧化物表面,并与碳纸基底复合形成催化活性层的设置,使得活性位点以低配位团簇形态高度分散于载体表面,从而在电催化二氧化碳还原反应中实现了较高的甲烷法拉第效率。
Smart Images

Figure CN122959784A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical engineering technology, specifically to a supported oxygen-containing copper cluster catalyst and its application in the electrocatalytic synthesis of methane. Background Technology
[0002] The technology of electrochemically catalytically converting carbon dioxide into methane emerged in response to the dual challenges of global carbon cycle imbalance and the urgent need for renewable energy utilization. With the long-term, large-scale use of fossil fuels leading to a sharp rise in carbon dioxide concentrations, traditional carbon capture and storage (CCS) technologies, while partially mitigating direct emissions, cannot achieve effective recycling of carbon resources. Meanwhile, the rapid development of renewable energy sources such as wind and solar power, while offering possibilities for energy structure transformation, has resulted in severe wind and solar curtailment due to their inherent intermittency and volatility, necessitating efficient, large-scale energy storage technologies. Against this backdrop, utilizing electricity generated from renewable energy sources to electrochemically reduce carbon dioxide to methane under mild conditions not only converts greenhouse gases into storable chemical energy but also fully utilizes existing natural gas infrastructure for storage and transportation, becoming a crucial technological pathway for constructing an artificial carbon cycle and supporting renewable energy utilization.
[0003] In recent years, despite the rapid advancements in nanoscience and characterization techniques that have propelled research in this field from macroscopic trial-and-error to precise atomic-scale design, copper-based catalysts, as the mainstream choice for the reduction of carbon dioxide to methane, still face significant challenges in balancing activity, selectivity, and stability. Although efficiency has been improved to a high level through nanotechnology, these high-performance catalysts are often limited by narrow potential windows and low current density conditions, making it difficult to achieve industrial-grade current densities (>200 mAcm⁻¹). -2 It maintains excellent selectivity under certain conditions. However, as the current density increases, the competition for hydrogen evolution reaction intensifies, becoming a key factor restricting the selectivity of methane and leading to a significant decrease in the efficiency of the target product. In addition, the catalyst is prone to deactivation phenomena such as valence state changes, surface reconstruction, particle agglomeration, and active site poisoning during long-term operation, which further limits the feasibility of its industrial-scale application. Therefore, it is necessary to improve it. Summary of the Invention
[0004] The purpose of this invention is to provide a supported oxygen-containing copper cluster catalyst and its application in the electrocatalytic synthesis of methane, so as to solve the problem that copper-based catalysts in the prior art cannot achieve both methane selectivity and long-term stability at high current densities.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a supported oxygen-containing copper cluster catalyst, comprising a carbon paper substrate and a catalytic active layer formed on the carbon paper substrate, wherein the catalytic active layer comprises oxygen-containing copper clusters supported on rare earth metal oxides, and the surface of the oxygen-containing copper clusters is modified with organic modifying molecules.
[0006] Furthermore, the organic modified molecule is selected from one or more of thiols, amines, alcohols, or alkanes.
[0007] Furthermore, the thiol compound is selected from at least one of propanethiol, hexanethiol, or octanethiol.
[0008] Furthermore, the rare earth metal oxide is selected from one or more of lanthanum oxide, cerium oxide, neodymium oxide, samarium oxide, gadolinium oxide, holmium oxide, erbium oxide, or thulium oxide.
[0009] Furthermore, the mass ratio of the oxygen-containing copper cluster to the rare earth metal oxide is 100:1 to 1:1.
[0010] Furthermore, the catalyst is prepared by a method comprising the following steps:
[0011] S1. Electrochemical deposition is performed on the surface of carbon paper under constant current conditions in an electrolyte containing copper precursor, rare earth metal precursor, acetate and citric acid, using carbon paper as the cathode, to form a precursor layer; wherein the copper precursor is selected from at least one of copper sulfate, copper nitrate, copper chloride, copper acetate, copper acetylacetonate and their hydrates; and the rare earth metal precursor is selected from at least one of rare earth metal nitrates and their hydrates.
[0012] S2. The product obtained in step S1 is immersed in a solution containing the organic modified molecules for surface modification;
[0013] S3. The product obtained in step S2 is subjected to in-situ electrochemical reduction and reconstruction in an alkaline electrolyte to obtain the supported oxygen-containing copper cluster catalyst.
[0014] The application of a supported oxygen-containing copper cluster catalyst in the electrocatalytic synthesis of methane includes the following steps:
[0015] In the electrochemical reaction apparatus, the supported oxygen-containing copper cluster catalyst is used as the working electrode, and an alkaline solution is used as the electrolyte. Carbon dioxide is introduced into the electrolyte, and an electrolysis reaction is carried out under constant current conditions to reduce carbon dioxide and generate methane.
[0016] Furthermore, the current density under the constant current condition is -300 mA cm⁻¹. -2 to -700mA cm -2 .
[0017] Furthermore, the alkaline solution is an aqueous solution of KOH or NaOH.
[0018] Compared with the prior art, the present invention provides a supported oxygen-containing copper cluster catalyst and its application in electrocatalytic synthesis of methane. By loading oxygen-containing copper in cluster form on the surface of rare earth metal oxide and combining it with a carbon paper substrate to form a catalytic active layer, the active sites are highly dispersed on the support surface in the form of low-coordination clusters, thereby achieving a high methane Faraday efficiency in the electrocatalytic carbon dioxide reduction reaction.
[0019] By introducing organic modifying molecules onto the surface of oxygen-containing copper clusters for interfacial modification, a ligand-mediated electron channel was constructed between the rare earth metal oxide support and the oxygen-containing copper clusters, thereby stabilizing the valence state of the copper active sites and suppressing the hydrogen evolution competition reaction under high current density conditions.
[0020] By selecting organic modification molecules from thiol compounds, the formation of Cu-S bonds between sulfur atoms and the surface of copper clusters enhances the hydrophobicity of the catalyst surface, reduces the enrichment of water molecules near the active site, and further suppresses the hydrogen evolution side reaction.
[0021] By selecting lanthanum oxide as the rare earth metal oxide, the interfacial synergy between lanthanum oxide and oxygen-containing copper clusters was utilized to promote the adsorption stability of the key intermediate CO at copper sites, thereby optimizing the reaction pathway of CHO hydrogenation to CH2OH. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this invention. For those skilled in the art, other drawings can be obtained based on these drawings.
[0023] Figure 1 HT@O-Cu in Embodiment 1 of the present invention c Schematic diagram of the synthesis of / La2O3;
[0024] Figure 2 HT@O-Cu in Embodiment 1 of the present invention c / La2O3 and unmodified O-Cu c Scanning electron microscope (SEM) image of / La2O3 and inset of contact angle;
[0025] Figure 3 HT@O-Cu in Embodiment 1 of the present invention cTransmission electron microscopy (TEM) and high-magnification transmission electron microscopy (HRTEM) images of La2O3;
[0026] Figure 4 HT@O-Cu in Embodiment 1 of the present invention c Aberration-corrected electron microscopy image of / La2O3;
[0027] Figure 5 HT@O-Cu in Embodiment 1 of the present invention c Elemental distribution map of La2O3 (EDS Mapping);
[0028] Figure 6 HT@O-Cu in Embodiment 1 of the present invention c / La2O3 and its unmodified O-Cu c Infrared spectrum of / La2O3;
[0029] Figure 7 The HT@O-Cu in Embodiment 1 of the present invention c / La2O3 and its unmodified O-Cu c Raman spectrum of La2O3;
[0030] Figure 8 The HT@O-Cu in Embodiment 1 of the present invention c XPS images of Cu 2p in La2O3 and its corresponding materials;
[0031] Figure 9 The HT@O-Cu in Embodiment 1 of the present invention c XPS images of La3d from La2O3 and its corresponding materials;
[0032] Figure 10 The HT@O-Cu in Embodiment 1 of the present invention c XPS plots of S 2p of La2O3 and its corresponding materials;
[0033] Figure 11 The HT@O-Cu in Embodiment 1 of the present invention c Figure 1.00 of Cu K-edge X-ray absorption fine structure (XAFS) measurement results for La2O3.
[0034] Figure 12 HT@O-Cu in Embodiment 1 of this invention c Cu Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum of / La2O3;
[0035] Figure 13 The HT@O-Cu in Embodiment 1 of the present invention cImage of La L3-edge X-ray absorption fine structure (XAFS) measurement results for La2O3;
[0036] Figure 14 HT@O-Cu in Embodiment 1 of this invention c / La Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum of La2O3;
[0037] Figure 15 HT@O-Cu in Embodiment 2 of the present invention c / La2O3 and O-Cu c Figure showing the long-term stability test results of / La2O3;
[0038] Figure 16 HT@O-Cu in Embodiment 3 of the present invention c / Graph of charge-difference electron transfer results in La2O3;
[0039] Figure 17 The HT@O-Cu in Embodiment 3 of the present invention c In-situ enhanced Raman spectrum of / La2O3;
[0040] Figure 18 HT@O-Cu in Embodiment 3 of the present invention c In-situ Fourier transform infrared spectrum of / La2O3. Detailed Implementation
[0041] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0042] As attached Figure 1 To be continued Figure 18 As shown:
[0043] Example 1:
[0044] This invention provides a supported oxygen-containing copper cluster catalyst and its application in the electrocatalytic synthesis of methane, using HT@O-Cu c The preparation of / La2O3 (c-representation cluster) catalyst is taken as an example.
[0045] Catalyst preparation:
[0046] La(NO3)3·6H2O (5.0 mM), Cu(NO3)2·3H2O (45.0 mM), sodium acetate (1.5 M), and citric acid (0.027 M) were added to the electrolytic cell to prepare an electrolyte solution with a total volume of 50 mL using deionized water as the solvent. A conventional three-electrode system was used for electrodeposition, with carbon paper (Sigracet-29BC, 2 × 2 cm²) as the working electrode (cathode), a nickel mesh as the counter electrode (anode), and an Ag / AgCl electrode (saturated KCl solution) as the reference electrode. Deposition was carried out at a constant current of 1.0 A for 50 s at room temperature, with continuous stirring during the deposition process to maintain the homogeneity of the electrolyte near the cathode. After deposition, the working electrode was removed, rinsed with deionized water, and dried under a nitrogen atmosphere to obtain O-Cu. c / La2O3 precursor electrode.
[0047] Subsequently, the above O-Cu c The La₂O₃ electrode was immersed in a solution containing 2 mL of hexamethylenetetramine (HT) dispersed in 10 mL of isopropanol at room temperature for 10 minutes. After immersion, the electrode was removed and thoroughly rinsed with anhydrous ethanol to remove excess unadsorbed HT from the surface, yielding m-HT@O-Cu. c / La2O3 electrical materials.
[0048] Next, the electrode was placed in a flow cell, using 1 M KOH aqueous solution as the electrolyte, and subjected to a constant current density of 500 mA / cm². -2 Under these conditions, an in-situ electrochemical reduction reaction is carried out for 30 seconds, causing in-situ reconstruction on the electrode surface to form the final HT@O-Cu. c / La2O3 catalyst (see preparation process) Figure 1 ).
[0049] Characterization of catalysts:
[0050] We are working with HT@O-Cu c The La2O3 catalyst was systematically characterized.
[0051] Scanning electron microscopy (SEM) and contact angle testing:
[0052] HT@O-Cu was studied using scanning electron microscopy. c / La2O3 and unmodified O-Cu c Morphological observation of / La2O3 was performed. Scanning electron microscopy images show that HT@O-Cu c / La2O3 exhibits an irregular blocky structure and is uniformly distributed on the carbon paper substrate. Contact angle test results show that HT@O-Cu c / La2O3 compared to unmodified O-Cu c / La2O3 catalysts exhibit enhanced hydrophobicity (see Figure 2 ).
[0053] Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM):
[0054] HT@O-Cu was studied using transmission electron microscopy. c Microstructural analysis of La₂O₃ was performed. Transmission electron microscopy (TEM) images showed that the catalyst morphology was consistent with the SEM results. High-resolution TEM images revealed lattice fringes with a spacing of 0.20 nm, which can be attributed to the crystal planes of La₂O₃ (see [link to TEM image]). Figure 3 ).
[0055] High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM):
[0056] High-angle annular dark-field scanning transmission electron microscopy with spherical aberration correction was used to study HT@O-Cu. c Atomic-scale imaging of / La2O3 was performed. HAADF-STEM images show HT@O-Cu. c / La2O3 is mainly composed of oxygen-containing Cu nanoclusters distributed on the surface of La2O3 (see Figure 4 ).
[0057] Energy dispersive spectroscopy (EDS) elemental distribution analysis:
[0058] Energy dispersive X-ray spectroscopy was used to study HT@O-Cu. c Elemental surface distribution scanning was performed on / La2O3. EDS mapping results further confirmed the presence of copper species in O-Cu. c The uniform dispersion of HT molecules on the La2O3 support, along with the uniform distribution of S elemental signal, indicates that HT molecules have achieved uniform modification on the catalyst surface (see [link]). Figure 5 ).
[0059] Fourier transform infrared (FTIR) and Raman spectroscopy analysis:
[0060] For HT@O-Cu c / La2O3 catalyst and its unmodified O-Cu c / La2O3 was characterized by Fourier transform infrared (FTIR) and Raman spectroscopy. Characteristic vibrational peaks attributable to hexathiol molecules were detected in both FTIR and Raman spectra, confirming that HT@O-Cu c / La2O3 catalyst contains La2O3 and O-Cu c Uniformly bonded HT molecules (see Figure 6 and Figure 7 ).
[0061] X-ray photoelectron spectroscopy (XPS) analysis:
[0062] X-ray photoelectron spectroscopy was used to study HT@O-Cu. c The surface chemical states of La₂O₃ and its corresponding comparative materials were analyzed. The Cu 2p spectrum showed characteristic peaks of mixed valence states of copper in the catalyst; the La 3d spectrum showed that La elemental composition was as follows: 3+ The presence of a valence state corresponds to the La2O3 phase; the S 2p spectrum detected a characteristic signal of S element, further confirming the successful modification of the catalyst surface by HT molecules (see...). Figures 8 to 10 ).
[0063] X-ray absorption fine structure (XAFS) analysis:
[0064] For HT@O-Cu c X-ray absorption fine structure analysis was performed on the La2O3 catalyst using Cu K-edge and La L3-edge spectra. Cu K-edge XANES and Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectra revealed that Cu species in the catalyst exist in clusters with significant Cu-O coordination characteristics. La L3-edge XANES and FT-EXAFS results confirmed the phase structure of the La2O3 support (see [link to XANES / FT-EXAFS]). Figures 11 to 14 ).
[0065] HT@O-Cu x Synthesis of La2O3 (x represents different Cu contents):
[0066] O-Cu x Electrodeposition of La2O3:
[0067] 50 mL of electrolyte, comprising metal nitrate (50.0 mM), CH3COONa (1.5 M), and C6H8O7 (0.027 M), was used during electrochemical deposition. Electrochemical deposition was performed at room temperature using a constant current (1.0 amperes) on a 2 × 2 cm² carbon paper (Sigract-29BC) substrate, with a nickel mesh as the anode. The electrolyte concentration near the cathode was adjusted by stirring. The concentration ratio of C (La) was... 3 + ): C(Cu) 2+ The ratios were adjusted to 48:2, 45:5, and 40:10 respectively for the manufacture of O-Cu / La2O3 and O-Cu. c / La2O3 and O-Cu NPs / La2O3.
[0068] The preparation processes of La₂O₃ and O-Cu are the same as described above, with the metal ions in the precursor solution consisting solely of La.3+ and Cu 2+ composition.
[0069] Immersion in HT solution:
[0070] O-Cu x The La2O3 electrode was immersed in isopropanol containing 2 mL of hexamethylenetetramine (HT) at room temperature for 10 minutes without stirring. Excess HT was removed by washing with ethanol to obtain m-HT@O-Cu. x / La2O3 electrode.
[0071] The catalysts were prepared by immersing La₂O₃ and O-Cu in isopropanol solution diluted with 2 mL of hydride for 10 minutes, respectively. Excess hydroxide was removed by washing with ethanol to obtain m-HT@La₂O₃ and m-HT@O-Cu electrodes.
[0072] In-situ electrochemical reduction and reconstruction:
[0073] Subsequently, m-HT@O-Cu x The La2O3 electrode was assembled as the cathode of a flow cell electrolyzer for in-situ reconstruction steps. The electrode was operated in the flow cell at 500 mA / cm². -2 In-situ electrochemical reconstruction chronoamperometry was performed for 30 seconds at 1 mH⁺, followed by CO₂RR assessment. The resulting electrode was labeled HT@O-Cu. x / La2O3. Both HT@La2O3 and HT@O-Cu were prepared using the same method described above.
[0074] Example 2:
[0075] This embodiment is essentially the same as the previous embodiment, except that all electrochemical experiments were performed on an electrochemical workstation (CHI 760E, Shanghai Chenhua Instrument Co., Ltd.) and a high-current amplifier (CHI 680C, Shanghai Chenhua Instrument Co., Ltd.). The electrolysis experiment was conducted in a flow cell at 25°C using a three-electrode system. The three electrodes included a working electrode, a nickel mesh counter electrode, and an Ag / AgCl reference electrode. The reference electrode was stabilized by a glass tube with a Luggin capillary and filled with saturated KCl solution. Before the experiment, the reference electrode was calibrated according to the method described in the literature. An FAA-3-PK-130 membrane was used as the anion exchange membrane to separate the cathode and anode, and 1M KOH solution was used as the electrolyte. The electrolyte volume used in each experiment was 30 mL. During the electrolysis reaction, the electrodes were electrolyzed at a stable CO2 flow rate of 20 sccm. Gaseous products were collected using gas bags and analyzed using a gas chromatograph (GC, HP 4890D), while liquid products were analyzed using nuclear magnetic resonance (¹H-NMR, Bruker Avance III 400 HD).
[0076] Test conditions description:
[0077] The CHI 760E electrochemical workstation is used to control the potential and current parameters during electrolysis, while the CHI 680C high-current amplifier is used to meet the electrolysis requirements under high current density conditions. The cathode and anode chambers of the flow cell are separated by an FAA-3-PK-130 anion exchange membrane. CO2 gas is introduced into the cathode chamber, and the working electrode and reference electrode are installed there. The counter electrode is installed in the anode chamber, and an equal volume of electrolyte is added. The Luggin capillary tip of the reference electrode is placed close to the surface of the working electrode to reduce the influence of the solution ohmic drop on the potential measurement.
[0078] The CO2 gas is humidified before entering the flow cell, and the gas flow rate is precisely controlled at 20 sccm using a mass flow controller. The electrolysis reaction is carried out in constant current mode, with the current density set at -300 mA cm⁻¹. -2 -400mA cm -2 -500mA cm -2 -600mA cm -2 and -700mA cm -2 The reaction time is 30 minutes at each current density.
[0079] Gas product analysis was performed using an HP 4890D gas chromatograph equipped with a thermal conductivity detector (TCD) and a flame ionization detector (FID). The TCD was used to detect hydrogen (H2), and the FID was used to detect carbon-containing gaseous products such as carbon monoxide (CO), methane (CH4), and ethylene (C2H4). A Porapak N packed column and a molecular sieve column were used in series, with high-purity argon as the carrier gas. External standard method was used for quantitative analysis of each gaseous product, and standard curves were pre-plotted using standard gases.
[0080] Liquid products were analyzed using a Bruker Avance III 400 HD nuclear magnetic resonance spectrometer with ¹H-NMR measurements. 0.5 mL of the electrolyzed cathode electrolyte was taken, and 0.1 mL of D₂O was added as a field-locking solvent, along with a known concentration of dimethyl sulfoxide (DMSO) as an internal standard. Formic acid, ethanol, and other components in the liquid products were quantitatively analyzed using the internal standard method.
[0081] Comparison of test results for different catalysts:
[0082] The experimental results of the electrocatalytic carbon dioxide reaction under different catalytic conditions are shown in Tables 1 to 3. It can be seen that the catalytic system of this invention has excellent selectivity for methane. Compared with other materials, HT@O-Cu... c / La2O3 exhibits the highest catalytic activity. The Faraday efficiency for methane is at -500 mA cm⁻¹.-2 Under constant current, the reaction yield reached 78.4% after 30 minutes. The current density at this potential reached 389.2 mA / cm². -2 It can react stably for more than 250 hours.
[0083] Table 1: Comparison of Faraday efficiency and current density for different catalysts in methane at different current densities.
[0084] Table 1 lists six different catalysts at -300 mA cm⁻¹ -2 to -700mA cm -2 Methane Faradaic efficiency (FE) in the current density range CH4 The data includes the actual achieved partial current density (j). The six catalysts are: unmodified O-Cu... c / La2O3, hexamethylenetetramine-modified HT@La2O3, hexamethylenetetramine-modified HT@O-Cu / La2O3, hexamethylenetetramine-modified HT@O-Cu c / La2O3, hexathiol modified HT@O-Cu NPs / La2O3 and HT@O-Cu modified with hexathiol.
[0085]
[0086] As shown in Table 1, at -500 mA cm -2 At current density, HT@O-Cu c The La₂O₃ catalyst achieved a maximum methane Faradaic efficiency of 78.41%, corresponding to a partial current density of 392.8 mA cm⁻¹. -2 Under the same conditions, unmodified O-Cu c The methane Faradaic efficiency of the La2O3 catalyst was only 39.78%, compared to 24.40% for HT@La2O3 and 35.83% for HT@O-Cu. This comparison indicates that the synergistic effect of the La2O3 support and oxygen-containing copper clusters, along with the surface modification with hexamethylenetetramine, jointly promoted the improvement in methane selectivity. Furthermore, HT@O-Cu... NPs The methane Faradaic efficiency of / La2O3 (containing oxygen-containing copper in nanoparticle form) is 55.85%, which is lower than that of the cluster morphology (78.41%), indicating that the cluster structure of oxygen-containing copper has a significant impact on catalytic performance.
[0087] Table 2: Comparison of catalyst performance with different rare earth metal oxide supports
[0088] Table 2 lists the oxygen-containing copper cluster catalysts modified with hexamethylenetetramine using different rare earth metal oxides as supports at -500 mA cm⁻¹. -2The Faraday efficiency of methane at various current densities and some current density data. The rare earth metal oxides tested include La₂O₃, Ce₂O₃, Nd₂O₃, Sm₂O₃, and Gd₂O₃.
[0089]
[0090] As shown in Table 2, the catalyst supported on La2O3 exhibits the highest methane Faradaic efficiency (77.84%) and partial current density (389.2 mA cm⁻¹). -2 The catalyst supported on Ce₂O₃ showed the second highest faraday efficiency for methane, at 58.49%. Catalysts supported on Nd₂O₃, Sm₂O₃, and Gd₂O₃ showed faraday efficiencies of 45.30%, 40.92%, and 40.08%, respectively. These results indicate that the rare earth metal oxides involved in this invention can all serve as effective supports for oxygen-containing copper clusters, with La₂O₃ showing the best performance.
[0091] Table 3: Comparison of catalyst performance with different organic modification molecules
[0092] Table 3 lists O-Cu modified with different organic molecules. c / La2O3 catalyst at -500mA cm -2 The Faraday efficiency of methane at various current densities and some current density data. The modified molecules tested included isopropanol (IPA), n-hexane (n-Hx), n-hexylamine (HxA), hexylthiol (HT), propanethiol (PT), and octylthiol (OT).
[0093]
[0094] As shown in Table 3, the catalyst modified with hexamethylenetetramine (HT) exhibits the highest methane Faradaic efficiency (77.84%) and partial current density (389.2 mA cm⁻¹). -2 The catalyst modified with n-hexylamine (HxA) showed the second highest methane Faradaic efficiency at 52.28%. Catalysts modified with isopropanol (IPA), n-hexane (n-Hx), and propanethiol (PT) achieved methane Faradaic efficiencies of 35.48%, 43.04%, and 41.51%, respectively. The catalyst modified with octylthiol (OT) exhibited the lowest performance, with a methane Faradaic efficiency of 7.57%. These results indicate that different types of organic modifying molecules can be used for surface modification of the catalysts of this invention, with hexylthiol among thiols showing the best modification effect.
[0095] Catalyst long-term stability test:
[0096] For HT@O-Cu cThe La2O3 catalyst underwent long-term stability testing under constant current density of -500 mA / cm². -2 The electrolyte was a 1M KOH aqueous solution, and the CO2 gas flow rate was 20 sccm. During the test, the current density changes were recorded at regular intervals, and gaseous products were collected to analyze the methane Faradaic efficiency. After 250 hours of continuous operation, no significant decrease was observed in the catalyst's current density or the methane Faradaic efficiency. See the results below. Figure 15 .
[0097] Example 3:
[0098] This embodiment is basically the same as the previous embodiment, except that it is at –500mA cm -2 The reaction was carried out continuously for 250 hours under constant current density to evaluate HT@O-Cu. c The long-term stability of La2O3 was observed. We found no significant changes in current density or the Faraday efficiency of methane. Figure 16 This indicates that no electrode passivation occurred. Simultaneously, interface modification using HT molecules formed a stable ligand-mediated electron channel between the La2O3 support and the oxygen-containing Cu cluster. This channel effect stabilizes the key low-coordinate Cu by modulating electron transfer. δ+ Active sites, synergistically optimizing reaction pathways. Ligand modification effectively stabilizes CO adsorption at copper sites and guides CHO hydrogenation to CH2OH (… Figure 17 and Figure 18 The electron channel effect also stabilized the Cu-C bond energy and promoted OH desorption. These results all indicate that the catalyst has good electrochemical stability and great industrialization value.
[0099] Long-term stability test conditions:
[0100] Long-term stability testing was conducted in a flow cell using the same three-electrode system as in Example 2. The working electrode was HT@O-Cu. c The electrode used was a La₂O₃ catalyst (effective area 1×1 cm²), with a nickel mesh as the counter electrode and an Ag / AgCl electrode (saturated KCl) as the reference electrode. The electrolyte was a 1M KOH aqueous solution, with 30 mL added to each of the cathode and anode chambers. During the test, CO₂ gas was introduced into the cathode chamber at a constant flow rate of 20 sccm. Electrolysis was performed at a constant current density of –500 mA cm⁻¹. -2 The experiment was conducted continuously for 250 hours under the specified conditions. During the test, gaseous products were collected every 24 hours, and the Faraday efficiency was analyzed using a gas chromatograph (GC, HP 4890D). Simultaneously, the cell voltage changes during the electrolysis process were recorded to monitor the electrode status.
[0101] Stability test results:
[0102] During a continuous 250-hour electrolysis test, HT@O-Cu c The current density of the La2O3 catalyst remained stable at 389.2 mA cm⁻¹. -2 Near the target area, the methane Faraday efficiency remained around 77.8%, with no significant decline observed. After the test, the working electrode was removed for SEM characterization, revealing that the catalyst surface morphology was essentially the same as before the reaction, with no obvious particle agglomeration or active material detachment observed. These results indicate that the catalyst exhibits good electrochemical stability under prolonged high current density conditions, without significant electrode passivation or catalyst deactivation.
[0103] In-situ enhanced Raman spectroscopy characterization:
[0104] To investigate the stabilizing effect of HT molecular interface modification on reaction intermediates, HT@O-Cu c The La2O3 catalyst was characterized by in-situ enhanced Raman spectroscopy. The tests were conducted on a confocal Raman spectrometer equipped with a 633 nm laser source, using a specially designed in-situ flow cell electrolysis device with 1 M KOH as the electrolyte, under a CO2-saturated atmosphere, and Raman spectra were collected at different potentials.
[0105] In-situ enhanced Raman spectrum (see) Figure 17 The results showed that, within the potential range of -0.5V to -0.8V (vs. RHE), a characteristic Raman peak (approximately 2080 cm⁻¹) attributable to the adsorption of CO intermediates on Cu sites could be observed. -1 The peak at 1730 cm⁻¹, and the characteristic peak attributable to the CHO intermediate (approximately 1730 cm⁻¹). -1 (At the site). As the potential shifts negatively, the intensity of the CO characteristic peak remains relatively stable, indicating that HT modification effectively stabilizes the adsorption of the CO intermediate at the Cu site. Meanwhile, at approximately 1050 cm⁻¹... -1 The presence of a Raman signal belonging to the CH2OH intermediate indicates that the reaction pathway proceeds towards methane formation.
[0106] In-situ Fourier transform infrared spectroscopy characterization:
[0107] For HT@O-Cu c The La₂O₃ catalyst was characterized by in-situ Fourier transform infrared spectroscopy (FTIR). Tests were performed on a Fourier transform infrared spectrometer equipped with an MCT detector, using an attenuated total reflectance (ATR) attachment coupled with an electrochemical in-situ cell. Test conditions: 1M KOH electrolyte, CO₂ saturated atmosphere, scan wavenumber range 4000–600 cm⁻¹. -1 The resolution is 4cm. -1 .
[0108] In-situ Fourier transform infrared spectrum (see) Figure 18 The results show that at a potential of -0.6V (vs. RHE), a peak can be observed at approximately 1650 cm⁻¹. -1 The absorption peak at approximately 1450 cm⁻¹ is attributed to the C=O stretching vibration of the CHO intermediate; -1 The absorption peak at approximately 1150 cm⁻¹ is attributed to the CH₂ bending vibration of the CH₂OH intermediate. -1 The absorption peak at this point is attributed to the CO stretching vibration of the COH intermediate. As the potential shifts negatively, the intensity of the characteristic peak of the CH2OH intermediate gradually increases, consistent with the increasing trend of the methane Faraday efficiency.
[0109] Charge density difference analysis:
[0110] To theoretically understand the regulatory effect of HT molecule interface modification on electronic structure, charge density difference calculations were performed. The calculations were conducted using density functional theory (DFT) in the VASP software package. A model of HT molecules adsorbed on O-Cu was constructed. c The structural model of the La2O3 surface was used to calculate the difference in charge density distribution before and after adsorption.
[0111] Results of charge density difference analysis (see) Figure 16 The study showed that HT molecules form Cu-S bonds with the Cu cluster surface through sulfur atoms, resulting in a redistribution of electron density in the Cu-S bond region, with some electrons transferring from Cu sites to HT molecules. This electron transfer effect stabilizes Cu. δ+ The low valence state of the coordination active site inhibits excessive reduction and aggregation of Cu sites at the reduction potential. Simultaneously, the formation of electron channels lowers the adsorption free energy of the CO intermediate at the Cu site and optimizes the energy barrier of the reaction pathway from CHO hydrogenation to CH2OH.
[0112] Comparative example:
[0113] Preparation and performance testing of supported oxygen-containing copper cluster catalysts without organic molecular modification.
[0114] Catalyst preparation:
[0115] This comparative example provides an oxygen-containing copper cluster catalyst (denoted as O-Cu) supported on lanthanum oxide without organic molecule modification. c / La2O3), its preparation includes the following steps:
[0116] Electrochemical deposition preparation of precursors:
[0117] Add 50 mL of electrolyte to the electrolytic cell. The electrolyte consists of the following components:
[0118] Copper nitrate trihydrate (Cu(NO3)2·3H2O): 45.0 mM;
[0119] Lanthanum nitrate hexahydrate (La(NO3)3·6H2O): 5.0 mM;
[0120] Sodium acetate (CH3COONa): 1.5M;
[0121] Citric acid (C6H8O7): 0.027M.
[0122] Using carbon paper (Sigracet-29BC, 2×2 cm²) as the working electrode (cathode), a nickel mesh as the counter electrode (anode), and an Ag / AgCl electrode as the reference electrode, electrochemical deposition was performed at room temperature in constant current mode. The deposition current was 1.0 A, and the deposition time was 50 seconds. Continuous stirring was maintained during deposition to adjust the electrolyte concentration near the cathode. After deposition, the carbon paper electrode was removed, rinsed with deionized water, and dried under a nitrogen atmosphere to obtain the precursor electrode.
[0123] In-situ electrochemical reduction and reconstruction:
[0124] The precursor electrode obtained by electrochemical deposition was placed in a flow cell, using 1M KOH aqueous solution as the electrolyte, and subjected to a constant current density of -500 mA / cm². -2 In-situ electrochemical reduction and reconstruction were performed under the specified conditions. The reconstruction lasted for 30 seconds. After reconstruction, the target catalyst O-Cu was obtained. c / La2O3.
[0125] The difference between this comparative example and Example 1 is that the organic molecule surface modification treatment was not performed by in-situ electrochemical reduction and reconstruction, that is, the hexamethylenetetramine immersion modification step was omitted.
[0126] Characterization of catalysts:
[0127] The O-Cu prepared in this comparative example c The La2O3 catalyst was characterized as follows:
[0128] Scanning electron microscopy (SEM) and contact angle testing:
[0129] The surface morphology of the catalyst was observed using scanning electron microscopy. The scanning electron microscopy images show O-Cu... c / La2O3 exhibits an irregular blocky structure and is uniformly distributed on the carbon paper substrate. Contact angle test results show that O-Cu c The contact angle of / La2O3 is significantly smaller than that of HT@O-Cu modified with hexathiol in Example 1. c / La2O3 catalyst, indicating that the unmodified catalyst surface has strong hydrophilicity (see Figure 2 ).
[0130] Fourier transform infrared (FTIR) and Raman spectroscopy analysis:
[0131] For O-Cu c / La2O3 was characterized by Fourier transform infrared (FTIR) and Raman spectroscopy. No characteristic vibrational peaks belonging to hexathiol molecules were detected in either the FTIR or Raman spectra, consistent with the HT@O-Cu in Example 1. c The spectral results for / La2O3 are compared (see...). Figure 6 and Figure 7 ).
[0132] X-ray photoelectron spectroscopy (XPS) analysis:
[0133] X-ray photoelectron spectroscopy was used to study O-Cu c The surface chemical state of La₂O₃ was analyzed. The Cu 2p spectrum showed characteristic peaks of mixed valence states of copper in the catalyst; the La 3d spectrum showed that La elemental composition was as follows: 3+ The valence state exists, corresponding to the La2O3 phase. Compared to Example 1, no characteristic signal of S element was detected in the S 2p spectrum (see [reference]). Figures 8 to 10 ).
[0134] Electrocatalytic carbon dioxide reduction performance test:
[0135] Test apparatus and conditions:
[0136] The electrochemical testing conditions were the same as in Example 2. The tests were conducted in a flow cell using a three-electrode system.
[0137] Working electrode: O-Cu c / La2O3 catalyst electrode (effective area 1×1cm²);
[0138] Counter electrode: Nickel mesh;
[0139] Reference electrode: Ag / AgCl electrode (saturated KCl solution);
[0140] Anion exchange membrane: FAA-3-PK-130;
[0141] Electrolyte: 1 M KOH aqueous solution, 30 mL each for the cathode and anode chambers.
[0142] During the test, CO2 gas was introduced into the cathode chamber at a constant flow rate of 20 sccm. The electrolysis reaction was conducted at a constant current density of -300 mA cm⁻¹. -2 -400mA cm -2 -500mA cm -2-600mA cm -2 and -700mA cm -2 The reaction was carried out under the specified conditions, with a reaction time of 30 minutes at each current density.
[0143] Product analysis and calculation methods:
[0144] Gaseous products were analyzed using a gas chromatograph (GC, HP 4890D), and liquid products were analyzed using 1H NMR (Bruker Avance III 400 HD). The method for calculating the methane Faraday efficiency was the same as in Example 2.
[0145] Test results:
[0146] At -500mA cm -2 O-Cu prepared in this comparative example under constant current density c The La₂O₃ catalyst exhibits a methane Faradaic efficiency of 39.78%, corresponding to a methane current density of 198.9 mA cm⁻¹. -2 Compared with HT@O-Cu in Example 1 c Performance of the La2O3 catalyst under the same conditions (methane Faraday efficiency 78.41%, partial current density 392.8 mA cm⁻¹) -2 Compared to catalysts without organic molecule modification, the methane selectivity of the catalysts is significantly reduced.
[0147] O-Cu at different current densities c The performance test results of the La2O3 catalyst are detailed in Table 1 (see Table 1 of Example 2, O-Cu). c (Data from the / La2O3 column). At all tested current densities, its methane Faraday efficiency was lower than that of HT@O-Cu. c / La2O3 catalyst. Specific data are as follows:
[0148] At -300mA cm -2 At that time, FE CH4 It is 31.29%, and j is 93.87 mA cm. -2 ;
[0149] At -400mA cm -2 At that time, FE CH4 It is 33.97%, and j is 135.88 mA cm. -2 ;
[0150] At -500mA cm -2 At that time, FE CH4 The value is 39.78%, and j is 198.9 mA cm. -2 ;
[0151] At -600mA cm -2 At that time, FE CH4 It is 32.12%, and j is 192.72 mA cm. -2 ;
[0152] At -700mA cm -2 At that time, FE CH4 It is 18.25%, and j is 127.75 mA cm. -2 .
[0153] Catalyst stability test:
[0154] At -500mA cm -2 Under constant current density, for O-Cu c Continuous electrolysis tests were conducted on the / La2O3 catalyst. The results showed that after 50 hours of continuous operation, the catalyst's current density and methane Faradaic efficiency exhibited a significant decrease, exceeding 30%. This is in contrast to the HT@O-Cu catalyst in Example 1. c Compared to the La2O3 catalyst, which can operate stably for more than 250 hours without significant degradation, the catalyst without organic molecule modification has significantly poorer stability.
[0155] Comparative analysis of results:
[0156] Comparing the performance data of Example 1 and the comparative example, we can see that:
[0157] Under the same testing conditions, O-Cu without organic molecular modification c The methane Faradaic efficiency of the La2O3 catalyst (39.78%) is only that of the HT@O-Cu catalyst modified with hexamethylenetetramine. c / About half of the La2O3 catalyst (78.41%);
[0158] The methane fractional current density of the unmodified catalyst (198.9 mA cm⁻¹) -2 The efficiency was also significantly lower than that of the modified catalyst (392.8 mA cm⁻¹). -2 );
[0159] The unmodified catalyst showed significant deactivation within 50 hours, while the modified catalyst could operate stably for more than 250 hours.
[0160] Contact angle tests show that the modified catalyst surface has enhanced hydrophobicity, which is beneficial for suppressing hydrogen evolution competition reactions;
[0161] XPS and FTIR / Raman spectroscopy confirmed the differences in surface chemical composition between the two, and the modified catalyst surface contained an HT molecular layer.
[0162] The above results demonstrate that organic molecule surface modification is a key feature for achieving high methane selectivity and long-term stability in the catalyst of this invention. Omitting this modification step will lead to a significant decrease in catalytic performance.
[0163] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A supported oxygen-containing copper cluster catalyst, comprising a carbon paper substrate and a catalytically active layer formed on the carbon paper substrate, characterized in that, The catalytic active layer comprises oxygen-containing copper clusters supported on rare earth metal oxides, and the surface of the oxygen-containing copper clusters is modified with organic modifying molecules.
2. The supported oxygen-containing copper cluster catalyst according to claim 1, characterized in that, The organic modified molecule is selected from one or more of thiols, amines, alcohols, or alkanes.
3. The supported oxygen-containing copper cluster catalyst according to claim 1, characterized in that, The thiol compound is selected from at least one of propanethiol, hexanethiol, or octanethiol.
4. The supported oxygen-containing copper cluster catalyst according to claim 1, characterized in that, The rare earth metal oxide is selected from one or more of lanthanum oxide, cerium oxide, neodymium oxide, samarium oxide, gadolinium oxide, holmium oxide, erbium oxide, or thulium oxide.
5. The supported oxygen-containing copper cluster catalyst according to claim 1, characterized in that, The mass ratio of the oxygen-containing copper clusters to the rare earth metal oxides is 100:1 to 1:
1.
6. The supported oxygen-containing copper cluster catalyst according to claim 1, characterized in that, The catalyst is prepared by a method comprising the following steps: S1. Electrochemical deposition is performed on the surface of carbon paper under constant current conditions in an electrolyte containing copper precursor, rare earth metal precursor, acetate and citric acid, using carbon paper as the cathode, to form a precursor layer; wherein the copper precursor is selected from at least one of copper sulfate, copper nitrate, copper chloride, copper acetate, copper acetylacetonate and their hydrates; and the rare earth metal precursor is selected from at least one of rare earth metal nitrates and their hydrates. S2. The product obtained in step S1 is immersed in a solution containing the organic modified molecules for surface modification; S3. The product obtained in step S2 is subjected to in-situ electrochemical reduction and reconstruction in an alkaline electrolyte to obtain the supported oxygen-containing copper cluster catalyst.
7. The application of a supported oxygen-containing copper cluster catalyst as described in any one of claims 1 to 6 in the electrocatalytic synthesis of methane, characterized in that, Includes the following steps: In the electrochemical reaction apparatus, the supported oxygen-containing copper cluster catalyst is used as the working electrode, and an alkaline solution is used as the electrolyte. Carbon dioxide is introduced into the electrolyte, and an electrolysis reaction is carried out under constant current conditions to reduce carbon dioxide and generate methane.
8. The application of the supported oxygen-containing copper cluster catalyst according to claim 7 in the electrocatalytic synthesis of methane, characterized in that, The current density under the constant current condition is -300 mA cm⁻¹ -2 to -700mA cm -2 .
9. The application of the supported oxygen-containing copper cluster catalyst according to claim 7 in the electrocatalytic synthesis of methane, characterized in that, The alkaline solution is an aqueous solution of KOH or NaOH.